Trace element analysis of fusel oil by microwave-induced plasma optical emission spectrometry - Gonçalves, Daniel Araujo; McSweeney, Tina; dos Santos, Mirian Cristina [UNESP]; Martines, Marco A. Utrera; Malmonge, Luiz Francisco [UNESP]; Donati, George L. (Bentham Science Publishers, 2017)
Background: Fusel oil is a mixture of higher alcohols produced as a minor fraction of the fermentation-distillation process in sugar and ethanol industries. It can be used as a fixating agent in cosmetics products, as solvent in the food industry, or recycled as fertilizer. Considering the effects of toxic elements contamination on the quality and safety of these products, and on the environment, an efficient method for elemental fusel oil analysis may find applications in many fields. In this work, we evaluate the application of microwave-induced plasma optical emission spectrometry (MIP OES) for trace element determinations in the fusel oil matrix. Methods: Simple external calibration with standard solutions prepared in either water or 1-propanol is evaluated. Undiluted fusel oil, and 1-propanol solutions containing 5 or 50% v v-1sample matrix are analyzed. The introduction of air into the plasma prevented potential carbon deposition on the torch and the optics, and contributed to minimizing background signals. Results: No matrix effects were observed for calibration with 1-propanol solutions even for determinations in the undiluted sample (recoveries between 90-109% for a 1.0 mg L-1spiking level). The MIP stability requires no sample preparation, which allows for lower limits of detection (LODs) and higher sample throughput. The LODs for Cd, Cr, Cu, Ni and Pb in 1-propanol are 0.03, 0.009, 0.01, 0.007 and 0.04 mg L-1, respectively. Conclusion: The MIP OES procedure described here is a simple, accurate and precise approach to trace element analysis of fusel oil.
Keywords: Copper accumulation; Fusel oil; Higher alcohols; Matrix effects; Nitrogen plasma; Organic solvent effects